Experimental Analysis and Modeling of NOx Emissions in Compression Ignition Engines Fueled with Blends of Diesel and Palm Oil Biodiesel (2016)
Este articulo muestra el desarrollo de un modelo de emisiones de NOx para motores Diesel, el cual fue publicado en los Proceedings of the International Conference on Vehicle Technology and Intelligent Transport Systems.